Leadership in turbulent times : cultivating diversity and inclusion in the higher education workplace - Jean-Marie, Gaëtane; Tran, Henry (Professor of education finance); Lopez, Ann E. (Studies in educational administration (Emerald Group Publishing), 2023)
Social movements and events such as the Black Lives Matter and Stop Asian Hate, the Supreme Court's ruling against the legality of employment discrimination against the LGBT population, and the growing diversity of the workforce serve as impetus for more diverse and engaging work contexts. Racial diversity issues such as the paucity of educators of color in the field, workload disparity workload across teacher demographics, the handling of student discipline and employment discrimination need confronting to create more diverse and inclusive workspaces. The second of two volumes, Leadership in Turbulent Times draws upon cutting edge theories and evidence-based strategies by integrating conceptual and empirical work addressing educational leadership in these unprecedented and turbulent times, with a particular focus on cultivating diversity and inclusion in the higher education workplace. Moving theory and practice towards real change, Leadership in Turbulent Times is a timely contribution towards the goal of providing resources for promoting diversity and inclusion to leaders, educators, researchers and policymakers within the field of Education.